2018
DOI: 10.1002/agr.21566
|View full text |Cite
|
Sign up to set email alerts
|

Farmer perceptions of risk in 2017

Abstract: Agribusinesses seeking to serve farmer clientele, as well as those buying products from the farm for processing or transport, need to understand the factors impacting on-farm decision making. A bestworst choice experiment was employed to determine farmer perceptions of five general risk areas: production, marketing, financial, human, and legal risks. Results indicate, on average, farmers were more concerned with traditional farm business risks (production, financial, and marketing risks) relative to human and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…The pairwise experimental design was chosen for its simplicity to reduce respondent fatigue and keep the telephone survey short enough to encourage participation. The presentation of only two attributes at a time greatly reduces complexity, as respondents only need to select the “best” rather than choosing both the best and the worst—worst can be inferred—thus simplifying the choice task for the participant (Byrd, Widmar, and Gramig, 2018; Thompson, Bir, and Widmar, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The pairwise experimental design was chosen for its simplicity to reduce respondent fatigue and keep the telephone survey short enough to encourage participation. The presentation of only two attributes at a time greatly reduces complexity, as respondents only need to select the “best” rather than choosing both the best and the worst—worst can be inferred—thus simplifying the choice task for the participant (Byrd, Widmar, and Gramig, 2018; Thompson, Bir, and Widmar, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…We used registrations from the years 2011-2019, which are available as polygon data, showing the crops grown in individual fields. The combined area of the data was 28,077 km 2 . We used the definition of specialty crops of the US Department of Agriculture [63] to select 63 specialty crops from the farmers' registrations.…”
Section: Training Datamentioning
confidence: 99%
“…Farmers face many risks in the form of adverse weather, pests, diseases, and changes in crop prices, laws, and regulations [1][2][3]. A first step in managing and minimizing many of these risks is often to select appropriate crops for the cultivated areas.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein to the work by Miller et al (1982), we would expect that internal managers (those that feel that outcomes are largely shaped by their own actions as opposed to outside sources) would view sources of risk differently than external managers. Thompson et al (2019) examined how farmers in the United States rate different risk management categories (production, marketing, financial, human, legal). They found that production risk was viewed as the most important, followed by financial and marketing risks.…”
Section: Introductionmentioning
confidence: 99%
“…They found that production risk was viewed as the most important, followed by financial and marketing risks. While the work by Thompson et al (2019) provides much needed insight into the broad categories of risk that are important to producers, it is still unknown how producers rate the various sources of risk that occur within these categories. For example, variability in production may be a function of rainfall variability, other natural disasters such as hail or flooding, or the presence of pests and disease that could affect crop yield.…”
Section: Introductionmentioning
confidence: 99%